Front end loader at Brechin Castle, Trinidad - (:unkn) unknown (My University, 2013)
Front end loader which loads sugar at the sugar warehouse at Brechin Castle.
Cataloger's title
Keywords: Sugar machinery -- Trinidad and Tobago